The emergence of a new medical model: the international division of labour and the formation of an international outsourcing chain in teleradiology. (1st October 2012) - Selma Venco
Abstract : This article analyses the international division of labour in medicine. The study starts from the premiss that time and space compression imposes itself as a fundamental analytical category in a situation where telematics premits the constitution of international outsourcing chains for a wide range of professional activities — even those with a high degree of specialisation. It focuses on the role of Brazil in the outsourcing of medical functions, specifically those involving imaging, and demonstrates how this enables the client companies to extend their domains by generating images in a global chain, starting in peripheral countries - in this case Africa, passing through Europe, and with the possibility of analysis taking place in South America.